Updates on WHO 5th edition classification, molecular characteristics and tumor microenvironment of adrenocortical carcinomas - Yuto Yamazaki; Yuta Tezuka; Yoshikiyo Ono; Fumitoshi Satoh; Hironobu Sasano; Takashi Suzuki (Endocrine Journal)
Discerning malignancy in adrenocortical tumors is clinically pivotal in the management of patients but has also been one of the most difficult areas in both clinical and pathology settings. The recently published WHO 5th edition “Endocrine and Neuroendocrine Tumours” recommends a diagnostic algorithm employing not only one but several proposed histopathological criteria—including the Weiss criteria and its revision and the Helsinki criteria—in addition to the Reticulin algorithm, the Ki-67 proliferative index, and others depending upon their histopathological features. On the other hand, the risk classification proposed by ENSAT (European Network of Study for Adrenal Tumors) in 2018 was primarily based on the Ki-67 proliferative index of carcinoma cells, especially focusing on whether or not postoperative or adjuvant chemotherapy could be administered. The recently reported results of the ADIUVO study, although preliminary, discuss the necessity of postoperative therapy with mitotane in patients with low-grade adrenocortical carcinomas (ACCs) after complete resection. In addition, recently reported comprehensive genetic analyses attempted to classify ACCs into four major molecular subtypes: (i) the Wnt/-catenin pathway, (ii) the p53/Rb1 pathway, (iii) the chromosomal maintenance/chromatin remodeling pathway, and (iv) the MMR (Mismatch repair) pathway. Among those, groups (i) and (ii) are more commonly detected in high-grade ACCs but it is also true that specific therapeutic targets based on the molecular characteristics of tumors have remained limited. In addition, possible effects of glucocorticoid excess in functional ACCs on the tumor microenvironment have also been examined, and the utility of immune checkpoint inhibitors is being explored at this juncture.